ABO Blood Type in Relation in Relation to Caries Experience and Salivary Physicochemical Characteristic among College Students at Al-Diwania Governorate in Iraq - Kadhum, Rania F; Diab, Ban S (Journal of Baghdad College of Dentistry, 2015)
Background: (ABO) Blood type have an effect on general health including oral health as salivary physicochemical characteristics differ among different type of blood and as consequence these affect the severity of dental caries. The aim of the present study is an assessment of the prevalence of caries experience among different blood type in relation to salivary physicochemical characteristic. Materials and Methods: Two hundred and fifty females’ college students in Al-Qadisyia University aged 18 years old were selected on random basis; they were divided to four groups according to their blood type, Dental experience was diagnosed and recorded according to DMFs (Mülemman, 1976) Index, this allows recording decayed lesion by severity. A sub sample was pooled for salivary analysis. Results: In the present study the blood type O was more common followed by B and A, whereas the less common was AB type, caries experiences (DMFs) and Ds component were found to be statistically significant among different blood types. The most sever grade of dental caries D3 and D4 were higher among type AB and lowest sever grade D1 among B blood type. While salivary flow rate significantly differ among differ blood type, viscosity higher but not significant among type AB. While salivary concentration of calcium and total protein were differ but not significant, opposite to alkaline phosphatase which was highly significant among different blood types. Conclusions: ABO blood type has an effect on salivary physical and chemical characteristic of saliva as effect on prevalence of caries.